2018
DOI: 10.1159/000495027
|View full text |Cite
|
Sign up to set email alerts
|

A Complete Absence of Missense Mutation in Myosin Regulatory and Essential Light Chain Genes of South Indian Hypertrophic and Dilated Cardiomyopathies

Abstract: Background: Myosin is a hexameric contractile protein composed of 2 heavy chains associated with 4 light chains of 2 distinct classes – 2 regulatory light chains (MYL2) and 2 essential light chains (MYL3). The myosin light chains stabilize the long alpha helical neck of the myosin head and regulate the myosin ATPase activities. Objectives: Mutations in MYL2 and MYL3 are reported to be associated with cardiomyopathies. However, there is no study available on these genes in Indian cardiomyopathies, and therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Our present comprehensive genetic analysis of the MYBPC3 gene in Indian HCM and DCM patients has given important insight into risk stratification. Based on our present and previous studies on sarcomere genes in Indian population, 23,24,34,35,45,[62][63][64][65][66][67] we fully agree that the mutations in myosin heavy chain and myosin binding protein C are the frequent causes of cardiomyopathies; therefore, these two genes should be screened first, secondly, the thin filament regulatory genes (TNNT2, TNNI3, and TPM1), and finally, the rarely involved genes like TTN, MYL2, MYL3, and ACTC. Importantly, it is not sufficient and advisable to screen only the known reported mutations, because we could miss unique, rare, and population-specific disease-causing mutations.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Our present comprehensive genetic analysis of the MYBPC3 gene in Indian HCM and DCM patients has given important insight into risk stratification. Based on our present and previous studies on sarcomere genes in Indian population, 23,24,34,35,45,[62][63][64][65][66][67] we fully agree that the mutations in myosin heavy chain and myosin binding protein C are the frequent causes of cardiomyopathies; therefore, these two genes should be screened first, secondly, the thin filament regulatory genes (TNNT2, TNNI3, and TPM1), and finally, the rarely involved genes like TTN, MYL2, MYL3, and ACTC. Importantly, it is not sufficient and advisable to screen only the known reported mutations, because we could miss unique, rare, and population-specific disease-causing mutations.…”
Section: Discussionsupporting
confidence: 76%
“…In our previous studies, we reported a few genetic variations in other sarcomere genes of Indian cardiomyopathy patients: Tropomyosin (α-TMP1), 45 Troponin I3 (TNNI3), 24,62 Troponin T2 (TNNT2), 34,63 Actin (ACTC), 64 Myosin (β-MYH7), 35,65,66 and MYL2 & MYL3. 67 Therefore, our present and previous studies clearly illustrated the prevalence and spectrum of variations in sarcomere genes and their associations in Indian populationwith cardiomyopathies. 23,24,34,35,45,[62][63][64][65][66][67] Our categorization as pathogenic variations relied on the result that we could detect those missense mutations exclusively in patients and their family members.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Apart from missense mutations, we identified a total of 16 silent or synonymous mutations (4 in both HCM and DCM, 4 in DCM, and remaining 8 are found to be polymorphic) (►Table 2), 2 intronic variations are being detected exclusively in cases. Further, this study data are compared with our previous datasets of seven other sarcomere genes, MYL3, TPM1, ACTC, TNNI3, TNNT2, MYBPC3, and MYL2, 8,14,35,[39][40][41][42] and found no additional causative mutation suggesting nonexistence of compound heterozygosity.…”
Section: Resultsmentioning
confidence: 95%